A Review of the Phytochemistry and Pharmacology of Phyllanthus urinaria L. - Geethangili, Madamanchi; Ding, Shih-Torng (Frontiers in Pharmacology, 2018)
The genus Phyllanthus (L.) is one of the most important groups of plants belonging to the Phyllantaceae family. Phyllanthus urinaria (L.) is an annual perennial herbal species found in tropical Asia, America, China, and the Indian Ocean islands. P. urinaria is used in folk medicine as a cure to treat jaundice, diabetes, malaria, and liver diseases. This review provides traditional knowledge, phytochemistry, and biological activities of P. urinaria. The literature reviewed for this article was obtained from the Web of Science, SciFinder, PubMed, ScienceDirect, and Google Scholar journal papers published prior to December 2017. Phytochemical investigations reveal that the plant is a rich source of lignans, tannins, flavonoids, phenolics, terpenoids, and other secondary metabolites. Pharmacological activities include anticancer, hepatoprotective, antidiabetic, antimicrobial, and cardioprotective effects. Thus, this present review summarizes the phytochemical constituents and their biological activities including biological studies on various crude extracts and fractions both in vitro and in vivo, and on clinical trial information about P. urinaria. This review compiles 93 naturally occurring compounds from P. urinaria along with their structures and pharmacological activities. The review is expected to stimulate further research on P. urinaria, and its pharmacological potential to yield novel therapeutic agents.